An Investigation into the Vaccine for Covid-19 Within the United States - Femi Obasun (Open Journal of Trauma - Peertechz Publications, 2020)
This report looks into the current situation with regard to administering of Covid-19 vaccines within the United States and makes suggestions on how to aid the decision-makers' process. The study method is based on a review of existing data on Covid-19 vaccines and their effectiveness in eliminating the possibility of getting infected by the virus. The procedure utilizes the corresponding (incomplete) data that could theoretically be used in other decision-making methods. The review discovered that the information provided by the vaccine manufacturers is somewhat vague. The process entails predicting the future trend in Covid-19 mutation and the effectiveness of the existing vaccines in controlling the disease. The study interviewed 1200 vaccinated patients to give an opinion based on the patients.